Hepatitis viruses (other than hepatitis B and C viruses) as causes of hepatocellular carcinoma: an update. Issue 3 (26th December 2012) - Kew, M. C.
Summary Chronic hepatitis B and C virus infections are universally accepted as causes of hepatocellular carcinoma in humans. Hepatitis A and E viruses cause only acute self‐limiting infections of the liver. Of the remaining hepatitis viruses ‐ Delta hepatitis, hepatitis G (GB‐C), TT and SEN ‐ all have at some time been incriminated as causes of hepatocellular carcinoma. Delta hepatitis virus requires helper functions from hepatitis B virus to become invasive. Chronic Delta/hepatitis B viral co‐infection runs a more severe course than that resulting from chronic hepatitis B virus infection alone, with progression to cirrhosis being more likely and more rapid. A substantial majority of the early studies did not find an increased incidence of hepatocellular carcinoma in co‐infected individuals. But more recently, an increased incidence of the tumour has been recorded more often than no increase. Further studies are needed to draw a firm conclusion with regard to the hepatocarcinogenic effect of dual Delta/hepatitis B virus co‐infection. With one exception, no published study (of 13) has incriminated chronic infection with hepatitis G virus as a cause of hepatocellular carcinoma. The dissenting study, published in 1999, was the only one performed in the United States. Fewer studies of the hepatocarcinogenic effect of TT virus have been performed. Apart from one study, published in 1999, no convincing evidence is available that supports a causal role for TT virus in hepatocarcinogenesis. The exception was in Japanese patients with high hepatitis C viral loads but independent of chronic hepatitis C virus infection. No evidence has been produced to indicate that SEN virus causes hepatocellular carcinoma.